Pertimbangan Hukum Hakim Dalam Memutus Perkara Pembunuhan Berencana dengan Motif Persembahan Upacara Adat oleh Suku Noaulu Maluku Tengah (Studi Terhadap Putusan Nomor 87/Pid.B/2005/PN.Msh dan Putusan Nomor 25/PID/2006/PT. MAL) - Thaufik Amirullah (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract The position of customary law is the law of life and thrive in the community. However, if customary law is not contrary to the interests of national law it is considered to remain in effect, however, on the contrary if it is considered customary law contrary to positive law or national law, the provisions of the applicable law it is written. Persintuhan between customary law and national law in the context of law enforcement (law ​​enforcement) certainly become part of the discourse of academic study in the field of criminal law in Indonesia. The conflict between the two laws in the domain of formal legal action would have been triggered judicial settlement mechanisms which tend to use aspects of the litigation that has formal characteristics. Subject is deemed reasonable given that adheres to the principles of criminal law,